2020
DOI: 10.1093/mnras/staa623
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to the ‘basic’ HOD model and beyond

Abstract: We make use of the IllustrisTNG cosmological, hydrodynamical simulations to test fundamental assumptions of the mass-based Halo Occupation Distribution (HOD) approach to modelling the galaxy-halo connection. By comparing the clustering of galaxies measured in the 300 Mpc TNG box (TNG300) with that predicted by the standard ("basic") HOD model (bHOD), we find that, on average, the bHOD model underpredicts the real-space correlation function in the TNG300 box by ∼ 15% on scales of 1 Mpc/h < r < 20 Mpc/h, which i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 93 publications
(105 reference statements)
10
119
0
Order By: Relevance
“…As such, our technique has a stronger physical motivation, as real QSOs are characterised by a high BH accretion rate and strong clustering. Thus, unlike in Sorini et al (2018), our method provides a good match to the observed QSO clustering properties (White et al 2012) without assuming a purely mass-based HOD, which can be simplistic (Beltz-Mohrmann et al 2020;Hadzhiyska et al 2020). At the same time, the number of haloes that we select is the same that we would have selected if we had simply considered all haloes with mass above M min .…”
Section: Selection Of Qsos In Smentioning
confidence: 99%
“…As such, our technique has a stronger physical motivation, as real QSOs are characterised by a high BH accretion rate and strong clustering. Thus, unlike in Sorini et al (2018), our method provides a good match to the observed QSO clustering properties (White et al 2012) without assuming a purely mass-based HOD, which can be simplistic (Beltz-Mohrmann et al 2020;Hadzhiyska et al 2020). At the same time, the number of haloes that we select is the same that we would have selected if we had simply considered all haloes with mass above M min .…”
Section: Selection Of Qsos In Smentioning
confidence: 99%
“…In previous works, we found that conditioning on this parameter in TNG leads to a substantial increase in the galaxy clustering on large scales (Hadzhiyska et al 2020(Hadzhiyska et al , 2021a. We conjectured that at a fixed mass, haloes residing in denser regions contain more galaxies on average than haloes in underdense regions due to experiencing more mergers and having a larger gas reservoir with which to form stars (Abbas & Sheth 2007;Pujol et al 2017;Paranjape, Hahn & Sheth 2018;Shi & Sheth 2018).…”
Section: Halo Environmentmentioning
confidence: 65%
“…In this section, we review the definitions of the various halo parameters employed in this study (for more details, see Hadzhiyska et al 2020). Appendix B discusses the correlations between the various parameters in addition to the halo assembly bias measured for concentration and environment.…”
Section: Assembly Bias Parametersmentioning
confidence: 99%
See 2 more Smart Citations